Critical considerations for COIL practitioners in Higher Education: A review of literature from South Africa, the Global South and developing spaces. - Frankish, Tarryn; Ngubane, Sphelele; Alcock, Andrea (Critical Studies in Teaching and Learning, 2025)
In this paper, we conduct a collaborative autoethnography to guide our reading of text on collaborative, international online projects in higher education and in South Africa. Our reading reveals patterns that speak to critical considerations for those planning projects in the context or from similar positions within the Global South or other developing contexts. As COIL practitioners in South Africa, we reflect on the literature from the unique situatedness of our learning and teaching environments and broader social context. The insights we offer will help us to develop a toolbox that speaks to our positionality as academics and the intersectional dynamics of our sociopolitical subjectivities. Researchers and academics from the Global South and other developing spaces may find that the issues raised may resonate with their own collaborative, online international engagements as we try to speak into the bigger structures that we must consider when we engage in this work.